Dispersible Colloid Facilitated Release of Organic Carbon From Two Contrasting Riparian Sediments - Rod, Kenton A.; Patel, Kaizad F.; Kumar, Swatantar; Cantando, Elizabeth; Leng, Weinan; Kukkadapu, Ravi K.; Qafoku, Odeta; Bowden, Mark; Kaplan, Daniel I.; Kemner, Kenneth M. (Frontiers in Water, 2020)
In aqueous systems, including groundwater, nano-colloids (1-100 nm diameter) and small colloids (<450 nm diameter) provide a vast store of surfaces to which organic carbon (OC) can sorb, precluding its normal bioavailability. Because nanomaterials are ubiquitous and abundant throughout Earth systems, it is reasonable that they would play a significant role in biogeochemical cycles. As such, mineral nano-colloids (MNC) and small colloids, formed through mineral weathering and precipitation processes, are both an unaccounted-for reservoir and unquantified vector for transport of OC and nutrients and contaminants within watersheds. Water extractions and leaching experiments were conducted under 1) aerobic (ambient) and 2) anaerobic (environmental chamber) conditions for each of two contrasting riparian sediments from 1) Columbia River, Washington and 2) Tims Branch, South Carolina. Water dispersible colloid-adsorbed OC was as high as 48% of OC for Tims Branch anaerobic batch water extraction and as low as 0% for Columbia River aerobic batch water extractions. Anaerobic leaching from column experiments yielded higher colloid and OC release rates. Transmission electron microscopy with electron dispersive spectroscopy mapping revealed organic carbon associated with aggregations of nano-particulate silicate minerals and Mossbauer identified nano-particulate goethite. This exploratory study demonstrates that mineral facilitated release of OC in riparian sediments is both significant and variable between locations.